Avaliação da lixiviação de proteína e minerais de rações comerciais para camarão em água de baixa salinidade - Viana, Diego Wescley Cavalcante (2024)
Leaching is a natural phenomenon that occurs when feeds come into contact with liquids, resulting in the loss of their physical, chemical, and nutritional properties. Feeds represent a significant production cost in aquaculture, and with the intensification of production, it is crucial to provide more suitable and balanced nutrition to meet the nutritional requirements of the species. In this context, the primary objective of this study was to assess the stability and leaching of nutrients in different types of commercial feeds subjected to low salinity water. Four commercial feeds were tested, including three pelleted and one extruded. Leaching was investigated in two types of water: control water (distilled water) and water from a low salinity pond used in shrimp farming, at intervals of 1 hour, 3 hours, and 12 hours. To conduct the experiment, 20-liter plastic boxes were used, containing approximately 5 liters of water, ensuring that the feeds were fully submerged. The experimental design included treatments with control water (C) and pond water (V), labeled as RC1, RC2, RC3, and RC4. Water parameters such as pH, salinity, electrical conductivity, ammonia, nitrite, total hardness, total alkalinity, magnesium, and potassium were analyzed at the beginning and end of each period. The feeds underwent analyses for protein, magnesium, and potassium levels. Physical analyses of the feeds included moisture content, permeability index (water absorption), dry matter leaching rate, water floatability, diameter, pellet length, and pellet quantity per kg of feed. The results revealed that leaching of feeds into water led to an increase in concentrations of salinity, electrical conductivity, ammonia, nitrite, magnesium, potassium, total hardness, total alkalinity, and a decrease in pH. Regarding the feeds, an increase in protein levels was observed after 1 hour of water exposure, followed by a reduction in subsequent hours. Magnesium and potassium concentrations decreased in all time intervals. As for feed characteristics, the extruded feed showed the highest quantity of pellets per kg of feed, the shortest pellet length, and floatability, while the pelleted feed exhibited the smallest diameter.